Українська експресіоністична меритократія кінця ХХ – початку ХХІ століття: поезія І. Римарука - Яструбецька, Галина Іванівна; Yastrubetska, Halyna I. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зроблено спробу на основі прикладів з біографії та аналізу поезії вмотивувати факт активізації експресіоністичного первня, його локалізації та оформлення у викінчену, структуровану систему в збірці «Бермудський трикутний» І. Римарука. Довести, що цьому процесу сприяли зовнішні (соціально-історичні) і внутрішні (духовно-психологічні) темпоральні чинники. Показати процес трансформації знака в експресіоністичний образ. In the article the attempt was made to involve the fact of activation of primary substance, laid down in the depths of human spirit and important to the expressionists in the works of Ihor Rymaruk (1958-2008). Taking into consideration the biographical examples and study of the poetry the fact should be argued – namely the fact of localization of this substance and structuring into the complete system in the book “Bermudskyi trykutnyk” (2007). It should be proved that external (social-historical) and internal (spiritual-psychological) temporal agents (reasons) were contributed to such a process. Taking into consideration the existential concepts of Albert Camus the way should be traced – namely the way of implacable integration of consciousness of the poet into the sphere of absurd and evolution towards the absurd personality with all consequences of worldview and aesthetic (poetry of Orphism and crisis) plan. It should be showed how expressionistic constants (pain, loneliness) are set in text with the help of grammatical, stylistic, significative means. Implying the hermeneutic method the peculiarity of the process should be determined – namely the process of transformation of the sign (aesthetic sign) to the expressionistic slovoobraz, autjrization of conventional artistic units.
Ukrainian Expressionistic Meritocracy of the End of the 20th Century – the Beginning of the 21st Century: Poetry of Ihor Rymaruk.
Keywords: Ігор Римарук; експресіонізм; абсурд; криза; ініціація; Ihor Rymaruk; Expressionism; absurd; crisis; estrangement; initiation